Răspunsuri

2014-08-18T22:52:59+03:00
1)n=2k

(-1)^2k  * (-2) + (-1) ^(2k+2) *3 - (-1)^(2 *2k+3)  * (-4)=

= (+1) * (-2) + (-1)^ 2k * (-1) ^2 *3 - (-1) ^4k * (-1)^3  *  (-4)=

= -2 + 1 * 1 * 3 - [ 1 * (-1) * (-4)]=

= -2 +3 -4=

= -6 +3 =-3

2)n=2k+1

(-1)^ (2k+1) * (-2) + (-1)^ (2k+1+2) *3 - (-1) ^[2(2k+1)+3] * (-4)=

=(-1)^2k * (-1) * (-2) + (-1) ^(2k +3) *3 - (-1) ^(4k+2+3) * (-4) =

= (+1) * (+2) + (-1) ^2k * (-1)^3 *3 - (-1) ^(4k+5) * (-4)=

= 2 + 1 * (-1) *3 - (-1) ^4k * (-1)^5 * (-4)=

= 2 -3 - [1 * (-1)*(-4)]=

= 2 -3 -4=

=2 -7=  -5
1 5 1